Emerging challenges in agriculture: Need for restructuring agronomy education - Mahapatra, B S; Pramanick, Biswajit (Indian Farming, 2021)
At the advent of numerous challenges in agriculture, it is high time to reshape the agronomy education. The agronomy education must provide enough exposure to the learners combating current and emerging challenges in agriculture. Education system should be restructured keeping the present day demand in agriculture with appropriate amalgamation of basic and applied knowledge. Case-study as well as problem-solving aptitude based curriculum must be given priority in agronomy education. This will make an agronomist confident enough to innovate cutting-edge technologies to combat emerging challenges in agriculture.